Environmental Impact of Indira Gandhi Canal Project in Rawatsar Tehsil of Hanumangarh District, Rajasthan - Khan, M A; Vangani, N S; Singh, Nepal; Singh, Surendra (Annals of Arid Zone, 2016)
In Rawatsar tehsil of Hanumangarh district, seepage from the Indira Gandhi canal system, excessive use of water in cultivated fields and accumulation of watcr in depressions have brought more than perceptible change in the environment through sub-soil water level rise, waterlogging and soil salinity. The field data and spectral characteristics of IRS-IB LISS Â FCCs reveal that nearly 165 sq. km (34.25%) of the IOtal command area is under waterlogging and soil salinity. The problems of the affected area have been categorised as slight (67.95 sq. km). moderate (3.37 sq. km), severe (93.67 sq. km) and very severe (36.76 sq. km). The areal extent of waterlogging and soil salinity is increasing every year. However, there is scope to arrest these problems using improved technologies of land and water resources management.